Pharmacological, electrochemical and drug–DNA interaction aspects of tridentate Schiff bases and their triphenylphosphine nickel(II) complexes. (5th September 2017) - Shabbir, Muhammad; Ahmad, Iqbal; Ismail, Hammad; Ahmed, Safeer; McKee, Vickie; Akhter, Zareen; Mirza, Bushra
Graphical abstract: Synthesis and characterization of nickel(II) complexes. Single crystal X-ray analysis of Ni(L1 )PPh3 revealed square planar geometry. Pharmacological investigations explored bioactive nature. Voltammetry showed reversible one ET diffusion controlled process. Strong compound- DNA interaction was observed. Abstract: The complexes N-(2-oxidophenyl) salicylideneiminatotriphenylphosphine nickel(II) (Ni(L1 )PPh3 ) and N-(2-sulfidophenyl)salicylideneiminatotriphenylphosphine nickel(II) (Ni(L2 )PPh3 ) have been synthesized from Schiff base ligands N-(2-oxidophenyl)salicylideneiminate)(H2 L1 ), N-(2-sulfidophenyl)salicylideneiminate)(H2 L2 ) and bistriphenylphosphine nickel(II) chloride. The synthons were characterized by elemental analysis, spectroscopic (FT-IR, 1 H, 13 C and & 31 P NMR) methods and electro-analytical techniques. Single crystal X-ray diffraction analysis of complex Ni(L1 )PPh3 revealed its square planar geometry where nickel being coordinated through tridentate Schiff base H2 L1 and triphenylphosphine ligands. The pharmacological activities (brine shrimp cytotoxicity, antitumor, DPPH, DNA damage, antibacterial & antifungal) of the Schiff bases (H2 L1 & H2 L2 ) and their nickel complexes (Ni(L1 )PPh3 & Ni(L2 )PPh3 ) were investigated along with drug–DNA interaction studies. Results of brine shrimp lethality and antitumor assay showed highly significant activities which correlate the cytotoxic effect that can be utilized as anticancerous agents. In DPPH assay two compounds (H2 L1 & Ni(L1 )PPh3 ) showed significant activity and the remaining two compounds (H2 L2 & Ni(L2 )PPh3 ) showed protective behaviour in DNA damage assay. Antifungal assay exhibited varying degree of activities with MIC value ranging from 50 to 200 µg/ml. Additionally, Ni(L2 )PPh3 was found to be broad spectrum antibacterial agent by showing antibacterial activity against all tested bacterial strains. Schiff bases and their nickel complexes were found electroactive in positive and negative potential ranges respectively, while having single electron transfer process. The compounds were found highly interactive towards DNA molecules with a binding strength of about 10 4  M −1 thus indicating their biological worth.